Synthesis of Pb-doped CdS quantum dot using SILAR method on mesoporous TiO2 layer - Yosita Sudswasd; Feng Liu; Taro Toyoda; Qing Shen; Witoon Yindeesuk (Journal of Physics Conference Series, 2021)
Abstract This research focuses on the fabrication of CdS quantum dot-sensitized solar cells (QDSCs). CdS quantum dots (QDs) were fabricated on a mesoporous TiO 2 electrode using a successive ion layer adsorption and reaction (SILAR) method and Pb doping concentrations (0, 2, 4, 10, 15, 20, 25 and 30 %mol) were varied. The change in optical properties of CdS QDs was found to be affected by Pb doping. The Pb-doped CdS QDSCs were determined under the illumination of 100 mWcm −2 , which indicated the highest power conversion efficiency (PCE) was 1.73% at 20% Pb dopant.
Keywords: Quantum Dots Synthesis And Properties; TiO2 Photocatalysis and Solar Cells; Chalcogenide Semiconductor Thin Films